Transcriptome analysis reveals molecular mechanisms responsive to acute cold stress in the tropical stenothermal fish tiger barb (Puntius tetrazona) - Liu, Lili (BMC Genomics, 2020)
BACKGROUND: Tropical stenothermal fish exhibit special tolerance and response to cold stress. However current knowledge of the molecular mechanisms response to cold stress in aquatic ectotherms is largely drawn from eurythermal or extreme stenothermal species. The tiger barb Puntius tetrazona is a tropical stenothermal fish, with great popularity in aquarium trade and research. RESULTS: To investigate the response mechanism of P. tetrazona to low temperature, fish were exposed to increasing levels of acute cold stress. Histopathological analysis showed that the brain, gill, liver and muscle tissues appeared serious damage after cold stress (13 °C). Brain, gill, liver and muscle tissues from control (CTRL) groups (27 °C) and COLD stress groups (13 °C) of eight-month fish (gender-neutral) were sampled and assessed for transcriptomic profiling by high-throughput sequencing. 83.0 Gb of raw data were generated, filtered and assembled for de novo transcriptome assembly. According to the transcriptome reference, we obtained 392,878 transcripts and 238,878 unigenes, of which 89.29% of the latter were annotated. There were 23,743 differently expressed genes (DEGs) been filtered from four pairs of tissues (brain, gill, liver and muscle) between these cold stress and control groups. These DEGs were mainly involved in circadian entrainment, circadian rhythm, biosynthesis of steroid and fatty acid. There were 64 shared DEGs between the four pairs of groups, and five were related to ubiquitylation/deubiquitylation. Our results suggested that ubiquitin-mediated protein degradation might be necessary for tropical stenothermal fish coping with acute cold stress. Also, the significant cold-induced expression of heat shock 70 kDa protein (HSP70) and cold-induced RNA-binding protein (CIRBP) was verified. These results suggested that the expression of the molecular chaperones HSP70 and CIRBP in P. tetrazona might play a critical role in coping with acute cold stress. CONCLUSIONS: This is the first transcriptome analysis of P. tetrazona using RNA-Seq technology. Novel findings about tropical stenothermal fish under cold stress (such as HSP70 and CIRBP genes) are presented here. This study contributes new insights into the molecular mechanisms of tropical stenothermal species response to acute cold stress. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12864-020-07139-z.